Allyl isothiocyanate depletes glutathione and upregulates expression of glutathione S-transferases in Arabidopsis thaliana - Øverby, Anders; Stokland, Ragni A.; Åsberg, Signe E.; Sporsheim, Bjørnar; Bones, Atle M. (Frontiers in Plant Science, 2015)
Allyl isothiocyanate (AITC) is a phytochemical associated with plant defense in plants from the Brassicaceae family. AITC has long been recognized as a countermeasure against external threats, but recent reports suggest that AITC is also involved in the onset of defense-related mechanisms such as the regulation of stomatal aperture. However, the underlying cellular modes of action in plants remain scarcely investigated. Here we report evidence of an AITC-induced depletion of glutathione (GSH) and the effect on gene expression of the detoxification enzyme family glutathione S-transferases (GSTs) in Arabidopsis thaliana. Treatment of A. thaliana wild-type with AITC resulted in a time- and dose-dependent depletion of cellular GSH. AITC-exposure of mutant lines vtc1 and pad2-1 with elevated and reduced GSH-levels, displayed enhanced and decreased AITC-tolerance, respectively. AITC-exposure also led to increased ROS-levels in the roots and loss of chlorophyll which are symptoms of oxidative stress. Following exposure to AITC, we found that GSH rapidly recovered to the same level as in the control plant, suggesting an effective route for replenishment of GSH or a rapid detoxification of AITC. Transcriptional analysis of genes encoding GSTs showed an upregulation in response to AITC. These findings demonstrate cellular effects by AITC involving a reversible depletion of the GSH-pool, induced oxidative stress, and elevated expression of GST-encoding genes.